Peran Ekstrakurikuler Pramuka dalam Pembentukan Karakter Siswa Kelas IV-V Sekolah Dasar Negeri 5 Mataram: - Putri, Sulistia Dwiana (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2024)
Scout extracurricular activities have an important role in shaping character, developing social skills, and providing valuable learning experiences for students in Elementary School. This study aims to explore the extracurricular role of Scouts in the education of grade 5 students at Mataram State Elementary SchooEkstrakurikuler Pramukal 5. The research method used is a case study involving direct observation, interviews, and document analysis. The data analysis in this study uses an interactive model from Miles, Huberman and Saldana with the stages of data condensation, data presentation and conclusion making. The validity of the data uses source triangulation. The results of this study show that the form of scout extracurricular activities which include marching lines, rope and semaphore can play a role in instilling students’ character. The character of students instilled in the implementation of scout extracurricular activities is discipline, responsibility, meticulousness, responsiveness & meticulousness and courage & loyal. The cultivation of student character is instilled through scout extracurricular activities using teaching methods, spontaneous assignments, cooperation, demonstrations, punishments, and fieldwork. The character that is grown through scout extracurricular activities can be seen in the daily life of students and teaching and learning activities in the classroom. The findings of this study provide a deeper understanding of the extracurricular contribution of Scouts in the context of primary education.